Disparate Effects of Stressors on Met-Enkephalin System Parameters and on Plasma Concentrations of Corticosterone in Young Female Chickens - Colin Guy Scanes; Krystyna Pierzchala-Koziec (Animals, 2024)
The effects of stressors were examined on Met-enkephalin-related parameters and plasma concentrations of corticosterone in 14-week-old female chickens. Water deprivation for 24 h was accompanied by a tendency for increased plasma concentration of Met-enkephalin while plasma concentrations of corticosterone were elevated in water-deprived birds. Concentrations of Met-enkephalin were reduced in the anterior pituitary gland and adrenal gland in water-deprived pullets while proenkephalin (PENK) expression was increased in both tissues. There were changes in the plasma concentrations of Met-enkephalin and corticosterone in pullets subjected to either feed withholding or crowding. Concentrations of Met-enkephalin were increased in the anterior pituitary gland but decreased in adrenal glands in pullets subjected to crowding stress. The increase in the plasma concentrations of Met-enkephalin was ablated when the chickens were pretreated with naltrexone. However, naltrexone did not influence either basal or crowding on plasma concentrations of corticosterone. In vitro release of Met-enkephalin from the anterior pituitary or adrenal tissues was depressed in the presence of naltrexone. It was concluded that Met-enkephalin was part of the neuroendocrine response to stress in female chickens. It was concluded that stress influenced the release of both Met-enkephalin and corticosterone, but there was not complete parallelism.